2013
DOI: 10.1016/j.learninstruc.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in developmental dyscalculia depend on diagnostic criteria

Abstract: Developmental dyscalculia (DD) is a learning difficulty specific to mathematics learning. The prevalence of DD may be equivalent to that of dyslexia, posing an important challenge for effective educational provision. Nevertheless, there is no agreed definition of DD and there are controversies surrounding cutoff decisions, specificity and gender differences. In the current study, 1004 British primary school children completed mathematics and reading assessments. The prevalence of DD and gender ratio were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 36 publications
7
80
3
6
Order By: Relevance
“…Finally, the variation in findings concerning gender differences seems to be dependent on the analyses methods used (Devine, Soltész, Nobes, Goswami, & Szücs, 2013). However, the frequency of girls and boys defined as having DD or MD does not suggest under-or over-representation (e.g., Devine et al, 2013;von Aster, 2000).…”
Section: Figure 2 Terminology Describing Risk Levels For Mathematicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, the variation in findings concerning gender differences seems to be dependent on the analyses methods used (Devine, Soltész, Nobes, Goswami, & Szücs, 2013). However, the frequency of girls and boys defined as having DD or MD does not suggest under-or over-representation (e.g., Devine et al, 2013;von Aster, 2000).…”
Section: Figure 2 Terminology Describing Risk Levels For Mathematicsmentioning
confidence: 90%
“…However, some studies have shown no gender effect on early number skills performance (e.g., , and no gender differences in predictions to later achievement level (Duncan et al, 2007;Jordan et al, 2006Jordan et al, , 2007Lepola, Niemi, Kuikka, & Hannula, 2005;Mazzocco & Thompson, 2005). Finally, the variation in findings concerning gender differences seems to be dependent on the analyses methods used (Devine, Soltész, Nobes, Goswami, & Szücs, 2013). However, the frequency of girls and boys defined as having DD or MD does not suggest under-or over-representation (e.g., Devine et al, 2013;von Aster, 2000).…”
Section: Figure 2 Terminology Describing Risk Levels For Mathematicsmentioning
confidence: 90%
“…The lack of agreement on criterion validity causes variability in measuring the prevalence of MLD. A recent review of 17 prevalence studies found that estimates ranged between 1.3% and 10.3% (À2 SD to À0.68 SD below the mean in terms of a normal distribution), and their mean was about 5-6% (Devine et al, 2013). The above makes it clear that the often-mentioned heterogeneity of MLD is partly a consequence of the heterogeneous (explicit or implicit) MLD definitions studies use.…”
Section: Mld and Ddmentioning
confidence: 99%
“…Ramaa (2002) states that dyscalculia's comorbidity with ADHD or dyslexia occurs in approximately one quarter of cases although comorbidity with dyslexia appears to produce the most profound impairments when compared to those with dyscalculia alone, or those with dyscalculia and ADHD. However, it is vitally important to have clear diagnostic criteria in order to understand the prevalence of dyscalculia (Devine et al, 2013).…”
Section: Dyscalculiamentioning
confidence: 99%